Encyclopedia of associations : Vol. 2 - Ruffner, Frederick G; Fisk, Margaret; Gale Research Company (Michigan : Gale Research Company, 1968)
A comprehensive list of national organizations described briefly, with names, addresses, and telephone numbers. Associations keep track of industry data for their members and may have valuable information on an industry that would not be found in standard business sources. Indexes include name of organization, key word, and geographic area.
v. 1. pt. 1-2. National Organizations of the U.S. -- v. 1. pt. 3. Name and keyword index. -- v. 2. Geographic and executive indexes.
Editor: 4th-5th ed., F. G. Ruffner; 6th-11th ed., M. Fisk.
Issued in 2 v., 1961; in 3 v., 1964-83, 1989- ; in 4 v., 1984, 1986-88; in 5 v., 1985: v. 1, National organizations of the U.S.; v. 2, Geographic and executive index; v. 3, 4th-5th eds., New associations; 6th- ed., New associations and projects; v. 4, 18th-22nd ed., International organizations; v. 5, 19th ed., Research activities and funding programs.
New associations and projects (varies), issued 4 months after v. 1, lists additional associations not included in v. 1.
Has inter-edition supplements: Updating service, issued twice a year 1985- lists changes to associations listed in v. 1 & 3; International organizations supplement to v. 4 issued annually 1987-88.
Rankings indexes issued with the 21st ed.- to provide ranked listings by membership size, staff size, annual budget, and founding date for organizations listed in v. 1.
Available online and in CD-ROM editions.
Keywords: Associations, institutions, etc. -- Directories; Associations, institutions, etc. -- United States -- Directories